Щодо розуміння категорії «кримінально-правова кваліфікація» - Лугіна, Наталія Анатоліївна; Корнійчук, Світлана Ігорівна (Сумський національний аграрний університет, 2021)
У статті досліджено розуміння кваліфікації в доктрині кримінального права, проаналізовано суттєві, змістові, структурні та функціональні особливості кваліфікації, визначено її поняття. Встановлено, що істотною ознакою кваліфікації, яка є системоутворюючою, оскільки визначає основне, ключове, сутність і зміст кваліфікації, визначає специфіку її властивостей, визначає обсяг її поняття, є кримінально-правова оцінка кримінального права. Інші кваліфікаційні ознаки згруповані в поняття навколо цієї важливої системоутворюючої ознаки. Найважливішим аспектом кваліфікації, що визначає її сутність і зміст, є оцінка того, що сталося, тобто оцінка злочинного діяння на основі положень кримінального закону, яка полягає в кримінально-правовій оцінці кримінального правопорушення. Суть кримінально-правової кваліфікації полягає в кримінальноправовій оцінці кримінально-правових фактів із метою забезпечення кримінально-правового впливу на особу, яка вчинила злочинне діяння, в тому числі його мети та соціально-правової ролі. Ця ознака також є підставою для відмежування кваліфікації від інших понять і процесів, діяльності у сфері застосування кримінального права. Визнавши кримінально-правову оцінку істотною ознакою кваліфікації, необхідно встановити специфічні ознаки, що утворюють поняття кваліфікації. Поняття кваліфікації прямо чи опосередковано пов’язане з оцінкою як істотною ознакою. Відсутність такого зв’язку свідчить про помилковість зарахування ознаки до тих, що визначають ознаки кваліфікації та становлять її поняття. Цей факт також обґрунтовує те, що зазначена істотна системоутворююча ознака «кримінально-правова оцінка» може бути використана як синонім «кваліфікації з кримінального права». Надано авторське визначення кримінально-правової кваліфікації, а саме: це діяльність правоохоронних органів і суду, яка здійснюється в рамках кримінально-правових відносин охоронного характеру і складається з нормативно врегульованих, конкретних, дієвих кримінально-правових оцінок юридичного факту щодо встановлення кримінально-правових ознак, визначення кримінально-правової норми, яка це передбачає, та встановлення відповідності фактичних ознак злочинного діяння ознакам конкретної кримінально-правової норми.

The article examines the understanding of qualification in the doctrine of criminal law, analyzes the essential, semantic, structural and functional features of qualification, defines its concept. It is established that an essential feature of the qualification, which is system-forming, as it determines the main, key, essence and content of the qualification, determines the specifics of its properties, determines the scope of its concept, is a criminal law assessment. criminal law. Other qualifying features are grouped into concepts around this important system-forming feature. We believe that the most important aspect of qualification, which determines its essence and content, is the assessment of what happened, ie the assessment of a criminal act on the basis of the provisions of criminal law, which is a criminal assessment of a criminal offense. law, seems to be the correct formulation of the concept of qualification in criminal law. The essence of criminal law qualification is a criminal law assessment of criminal law facts in order to ensure criminal law influence on the person who committed the crime, including its purpose and socio-legal role. This important feature of qualification is system-forming, because it determines the main, key, essence and content of qualification, determines the specifics of its properties, determines the scope of its concept. This feature is also the basis for distinguishing qualifications from other concepts and processes, activities in the field of application of criminal law. Other qualifications are grouped around this important system feature. Recognizing the criminal law assessment as an essential feature of qualification, it is necessary to establish the specific features that form the concept of qualification. The concept of qualification, directly or indirectly related to assessment as an essential feature. The absence of such a connection indicates the erroneousness of assigning a feature to those that define the characteristics of a qualification and constitute its concept. This fact is also substantiated by the fact that this essential system-forming feature “criminal law assessment” can be used as a synonym for “qualification in criminal law”. Qualification is carried out by the relevant entities – law enforcement agencies and the court, which is responsible for the preparatory investigation and recognition of the relevant criminal proceedings. Note that the subject of the offense, the victim, lawyers, scientists and others may also qualify as a criminal offense. However, the subjects of criminal law qualification can be independently only law enforcement officers and the court of power, as this qualification provides for coercive criminal influence on the person who committed the crime. The subject of qualification is an act of criminal law, namely: offense; an act that is not criminally illegal, but has a criminal-legal significance, and criminal behavior of a person regulated by the Criminal Code, which is not generally recognized in the science of criminal law. As noted, in the theory of criminal law, qualification is traditionally associated with the commission of a crime. At the same time, recently in the criminal law literature it is proposed to expand the subject of qualification in criminal law and to introduce into scientific and legislative terminology such terms as “criminal qualification”, “qualification of a criminal act”, “qualification of acts other than criminal” or “criminal law”, “assessment of personality behavior” etc. The Avor definition of criminal-legal qualification is given, namely it is necessary to understand activity of law enforcement bodies and court which is carried out within the limits of criminal-legal relations of protective character and consists of normatively regulated, concrete, effective criminal-legal assessments of the legal fact. determination of the criminal law norm which provides for it, and establishment of conformity of factual signs of a criminal act to signs of the concrete criminal law norm.
Keywords: кримінальне право; кваліфікація; сутність кваліфікації; кримінально-правова оцінка; підстави кримінально-правової кваліфікації; criminal law; qualification; essence of qualification; criminal law assessment; grounds for criminal qualification